Evaluation of comprehensive care for older adults in primary care services - Nádia Placideli; Elen Rose Lodeiro Castanheira; Adriano Dias; Pedro Alcântara da Silva; Josiane Lozigia Fernandes Carrapato; Patricia Rodrigues Sanine; Dinair Ferreira Machado; Carolina Siqueira Mendonça; Thais Fernanda Tortorelli Zarili; Luceime Olivia Nunes; José Fernando Casquel Monti; Zulmira Maria de Araújo Hartz; et al. (Revista de Saúde Pública, 2020)
ABSTRACT OBJECTIVE To evaluate the performance of comprehensive care for older adults in primary care services in the Brazilian Unified Health System in the state of São Paulo, Brazil. METHODS A total of 157 primary care services from five health regions in midwestern São Paulo responded, from October to December 2014, the pre-validated 2014 questionnaire for primary care services assessment and monitoring. We selected 155 questions, based on national policies and guidelines on this theme. The responses indicate the service performance in older adults’ care, clustered into three areas of analysis: health care for active and healthy aging (45 indicators, d1), chronic noncommunicable diseases care (89 indicators, d2), and support network in aging care (21 indicators, d3). Performance was measured by the sum of positive (value 1) or negative (value 0) responses for each indicator. Services were clustered according to k-means of the performance scores of each domain. After weighting the domains (Z tests), we estimated the associations between the scores of each domain and independent management variables (typology, planning and evaluation of services), with simple and multiple linear regression. RESULTS Chronic noncommunicable diseases care (d2) showed, for all clusters, better average performance (55.7) than domains d1 (35.4) and d3 (39.2). Service performance in the general area of planning and evaluation associates with the performance of older adults’ care. CONCLUSIONS The evaluated services had incipient implementation of comprehensive care for older adults. The evaluation framework can contribute to processes to improve the quality of primary health care.